EVALUASI BEBAN KERJA MENTAL PADA PERAKITAN TRIPOD DENGAN METODE PELATIHAN VIRTUAL REALITY DAN KONVENSIONAL - Alifia Latifah W, Risna
The development of digitalization in the industrial world is increasingly expanding to all facets of the company. One of the digitalization that is starting to emerge is VR-based training. Various studies show that training with VR can improve operator performance, but there are also those that state that the use of VR increases mental workload. However, these studies are limited to using only subjective measurements to measure mental workload in VR training. Therefore, this study aims to compare mental workload between VR and conventional training methods with physiological and subjective measurements. In addition, this study also assessed the feasibility of using VR as a training media in terms of usability and cost.